Respuestas

  • Usuario de Brainly
2013-11-29T02:37:37+01:00
Aplicando la REGLA DE L'HOPITAL

lim          (x³ -2x+1)    =  lim    [x³ -2x+1]'
x→+oo    4x³ + 2       x→+oo   [4x³+2]'


(*) [x³ - 2x + 1]' = 3x² - 2
(*) [4x³ +2]' = 12x²


lim          (x³ -2x+1)    =  lim    3x² - 2
x→+oo    4x³ + 2       x→+oo   12x²


lim          (x³ -2x+1)    =  lim    3 x²    -  2
x→+oo    4x³ + 2       x→+oo   12x²    12x²


lim          (x³ -2x+1)    =  lim    1    -  1
x→+oo    4x³ + 2       x→+oo   4     6x²


(*) Lim        1/x^n  =0
   x→+oo


=> lim          (x³ -2x+1)    =   1/4
     x→+oo    4x³ + 2    


Eso es todo!!!